Краєзнавчі дослідження І. Франка: історіографічні інтерпретації - Конта, Р. (Краєзнавство, 2016)
У статті розглядається питання висвітлення в історіографії краєзнавчих досліджень І. Франка. Аналізуються різні підходи до вивчення краєзнавчих праць вченого радянськими, діаспорними та сучасними українськими вченими. Визначаються особливості формування наукового знання про І. Франка як краєзнавця представниками різних історіографічних шкіл. The article examines the coverage in historiography the local studies of I. Franko. The author stresses that until recently this problem remained largely unnoticed by scientists. It was a minor and not so important in assessing the artistic heritage of the scientist in comparison with his achievements as a writer, poet, essayist, translator, public and political figure. Soviet scientists tendentiously evaluated I. Franko’s works. Their researches have been constructed on the basis of Marxist-Leninist methodology. The emphasis was on political beliefs of scientist, which were submitted through the prism of fighting against Ukrainian «bourgeois nationalists». Diaspora studies differed significantly from the Soviet ideological counterparts. But in these studies a problem of scientific research of local history of I. Franko did not allocated in separate theme. The studies of Modern Ukrainian scientists only partially have raised this issue. As a result, it does not allow to form a general vision of bottlenecks and prospects for further research of local studies of I. Franko. В статье рассматривается вопрос освещения в историографии краеведческих исследований И. Франко. Анализируются различные подходы к изучению краеведческих трудов ученого советскими, диаспорными и современными украинскими учеными. Определяются особенности формирования научного знания об И. Франко как краеведа представителями различных историографических школ.